2012
DOI: 10.1039/c2fo30030c
|View full text |Cite
|
Sign up to set email alerts
|

RAGE-dependent activation of gene expression of superoxide dismutase and vanins by AGE-rich extracts in mice cardiac tissue and murine cardiac fibroblasts

Abstract: Advanced glycation end products (AGEs) are stable compounds formed from initial Maillard reaction products. They are considered as markers for ageing and often associated with age-related, degenerative diseases. Bread crust represents an established model for nutritional compounds rich in AGEs and is able to induce antioxidative defense genes such as superoxide dismutases and vanins in cardiac cells. The aim of this study was to investigate to what extend the receptor for AGEs (RAGE) contributes to this respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…ROS production within cells can be upregulated when exposed to specific factors, such as high glucose levels or AGEs [ 5 , 11 ]. Increased ROS production, as well as increased RAGE signaling triggered by the presence of AGEs, can result in increased SOD expression [ 5 , 12 , 20 ]. SODs convert superoxides into hydrogen peroxide (H 2 O 2 ), which can be further reduced by peroxidases to rid the body of reactive oxygen stressors [ 21 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS production within cells can be upregulated when exposed to specific factors, such as high glucose levels or AGEs [ 5 , 11 ]. Increased ROS production, as well as increased RAGE signaling triggered by the presence of AGEs, can result in increased SOD expression [ 5 , 12 , 20 ]. SODs convert superoxides into hydrogen peroxide (H 2 O 2 ), which can be further reduced by peroxidases to rid the body of reactive oxygen stressors [ 21 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased PKC, ERK1/2, and ROS production can also promote ECM remodeling, denoted by increased collagen synthesis and MMP activity [ 5 , 15 , 16 , 17 , 18 ]. Increased superoxides generation AGE/RAGE signaling can be reduced by increased expression of SODs converting superoxides into hydrogen peroxide [ 19 , 20 , 21 ]. In addition to ROS production, the AGE/RAGE signaling cascade can elicit myofibroblast differentiation, marked by increased α-SMA expression, which has been shown to increase collagen matrix contraction [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that bread crust extract could activate SOD through the receptor for advanced glycation end products (AGEs). But high doses of bread crust extract are independent of AGE receptors, indicating that additional mechanisms are involved in the activation of SOD [ 52 ]. In our experiments, sublethal doses of ALA-PDT induced an antioxidant response by activation of SOD1 and SOD2, but the specific activation mechanism of SODs remained to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the consumption of the glycose-lysine MRP in the diet did not affect the hepatic antioxidant defence of Wistar rats, while some positive modifications (e.g., an increase in glutathione peroxidase) were detected in muscle (29%) and serum (400%), pointing to an improved antioxidant capacity after the consumption of those model MRP [ 48 ]. On the other hand, as previously mentioned, the work by Leuner et al [ 14 ] in mice and their cardiac fibroblasts demonstrated that bread crust feeding induced the activation of the antioxidant defence by the increase in the gene expression of superoxide dismutase. The authors suggested that bread crust might be a promising tool as a preconditioning agent to protect cardiac cells against ischemia–reperfusion damage.…”
Section: Resultsmentioning
confidence: 86%
“…A recent study developed in mice and cardiac fibroblasts derived from them have established that RAGEs (the best-characterized AGE-receptor) are activated by dietary bread crust-derived AGEs. Next, the induction of antioxidant defence through the activation of the gene expression of superoxide dismutase takes place, suggesting that bread crust might be useful as a preconditioning agent to protect cardiac cells against ischemia–reperfusion damage [ 14 ].…”
Section: Introductionmentioning
confidence: 99%